2013
DOI: 10.1186/1471-2334-13-532
|View full text |Cite
|
Sign up to set email alerts
|

Invasive pneumococcal infections in Vellore, India: clinical characteristics and distribution of serotypes

Abstract: BackgroundStreptococcus pneumoniae infection is a serious problem worldwide and the case fatality rate remains high. The aim of this study was to analyze the distribution of pneumococcal serotypes causing invasive pneumococcal disease (IPD), to survey the potential coverage of present and future vaccines, and to investigate differences between serotypes and groups of serotypes with regard to manifestation, case fatality rate, age, and other risk factors.MethodsIsolates from 244 consecutive patients with IPD we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 25 publications
(35 reference statements)
1
15
2
Order By: Relevance
“…36 Our serotype distribution differed from that reported in the global analysis in part due to the relatively high frequency of serotypes 2, 12A, 45, 18F and 8, which are not in any of the PCV formulations. Data from Bangladesh's neighboring countries, Nepal 37,38 and India, 39 also revealed diverse serotypes. The Indian study had 55 different serotypes among 244 IPD cases and Nepal had 17 serotypes among 42 isolates.…”
Section: Discussionmentioning
confidence: 93%
“…36 Our serotype distribution differed from that reported in the global analysis in part due to the relatively high frequency of serotypes 2, 12A, 45, 18F and 8, which are not in any of the PCV formulations. Data from Bangladesh's neighboring countries, Nepal 37,38 and India, 39 also revealed diverse serotypes. The Indian study had 55 different serotypes among 244 IPD cases and Nepal had 17 serotypes among 42 isolates.…”
Section: Discussionmentioning
confidence: 93%
“…4 The occurrence of nonvaccine (21.4%) serotypes (i.e., that are not included in PCV10, PCV-13 and PPV-23) is also consistent with the observations of other studies, reporting rates of 25.4% 4 and 27%. 17 The emergence of non-vaccine serotypes might presumably be a result of the introduction of recent clones or even a result of capsular switching of existing stain or by many single genetic changes. [18][19][20] This baseline information would be important in regions where the population is relatively naïve to the vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…A literature review published in 2013, with observations from other countries, addressed the issue of tropism of different pneumococcal serotypes: serotypes 1, 19A and 3 were identified as predominant for pneumococcal pneumonia but not for meningitis IPD during the post-PCV7 period [14]. A recent paper from India, not included in the review, reported that serotypes 1, 5 and 7F (three of the six additional serotypes in PCV13) caused more pneumonia than meningitis [15].…”
Section: Discussionmentioning
confidence: 99%